A highly selective and pH-tolerance fluorescent probe for Cu2+ based on a novel carbazole-rhodamine hybrid dye. (January 2019) - Jiao, Xiaojie; Xiao, Zhigang; Hui, Peiyi; Liu, Chang; Wang, Qing; Qiu, Xiaoying; He, Song; Zeng, Xianshun; Zhao, Liancheng
Abstract: The development of new fluorescent dyes has been a continuously interesting topic due to their wide applications in various optoelectronic, analytical and biological fields. In this paper, a novel xanthene dye CzR has been developed by hybridizing of the carbazole and rhodamine skeletons in one molecular. To regulate the optical properties of CzR, its N -methyl derivative MeCzR was prepared by the reaction of CzR with iodomethane. The absorption and emission properties of CzR and MeCzR were investigated in detail. Because the distribution positions of the positive charge within the chromophore are environment-dependent, the optical properties of the dye CzR are strongly pH-dependent. However, the optical properties of MeCzR are stable in water in a wide range of pH. To demonstrate the application of this novel dye, we synthesized the novel Cu 2+ -selective fluorescent probe MeCzR-Cu . The probe exhibited a specific ability to recognize the Cu 2+ ion over other chemically close ions and with a detection limit down to the nanomolar range. Meanwhile, the probe MeCzR-Cu is living cell membrane permeable and can be utilized as a practical vehicle for detecting Cu 2+ in complex cellular systems. Graphical abstract: Image 1 Highlights: A novel xanthene dye CzR and its N -methyl derivative MeCzR have been developed. The absorption and emission properties of CzR and MeCzR were investigated in detail. A novel Cu2+-selective fluorescent probe MeCzR-Cu has been prepared from MeCzR. The probe MeCzR-Cu can be utilized as a practical vehicle for detecting Cu 2+ imaging.